The renaissance and the new world - Caselli, Giovanni, 1939- (New York : P. Bedrick Books : Distributed in the USA by Harper & Row, 1986)
Presents, in text and illustrations, a range of people whose way of life reveals various aspects of the society developing in Europe and America from the fifteenth through the eighteenth centuries.
Bibliography: p. 48.
Keywords: Material culture -- Europe -- History -- Juvenile literature; Renaissance -- Juvenile literature; Renaissance; Europe -- Social life and customs -- Juvenile literature; Europe -- Social life and customs